Terrorism, Belief Formation, and Residential Integration: Population Dynamics in the Aftermath of the 2004 Madrid Terror Bombings. (September 2016) - Edling, Christofer; Rydgren, Jens; Sandell, Rickard
In this article, we study the effects of the 2004 terrorist bombings in Madrid on ethnic segregation in Spain. Using large-scale Spanish register data consisting of information on 5.4 million international migration events on a monthly basis and 13.9 million intermunicipal migration events, of which 3.8 million events concern the foreign-born population's internal migration within Spain, the analyses show that ethnic segregation increased (i.e., the average geographical distance) between Arab immigrants and native Spaniards shortly after the terror bombing, but that no such effect was found for other immigrant groups. The analysis also shows that this was a relative short-term effect: After about 1 or 2 years, ethnic segregation started to decline again (and thus resumed the declining trend that was observed during the years before the terrorist bombing). We interpret these results in terms of belief formation mechanisms. Because of priming and framing effects, the terrorist bombings accentuated the salience of ethnic categorizations and induced threat-attributing ethnic stereotypes, which were influencing migration behaviors. However, not only did native Spaniards become more reluctant to live in close proximity to Arab immigrants, Arab migrants also became more inclined to move closer to coethnics, possibly because of a perceived threat to become victims of discriminatory behaviors of the majority population. Priming and framing affects abated after a while, and migration behaviors started to return to normal again. Finally, we discuss a variety of survey data to substantiate the argument that belief formation mechanisms played an important role in these processes.